2021
DOI: 10.1111/bjep.12454
|View full text |Cite
|
Sign up to set email alerts
|

Whether verbal and visuospatial working memory play different roles in pupil’s mathematical abilities

Abstract: Background Previous research showed a significant association between mathematics and working memory (WM). However, evidence regarding the different effects of verbal and visuospatial WM on mathematical abilities was very limited. Aims The current research aims to explore the relationship between verbal and visuospatial WM with mathematical abilities, and how this relationship is moderated by age and math domains. We also wonder whether the results would change when we use several tests for each component and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
(64 reference statements)
3
13
0
Order By: Relevance
“…Our results, however, suggest the possibility that low-control VSWM also keeps a role in solving math tasks in older children. Our findings regarding the association between VSWM and math in older children are consistent with many studies showing that (i) the association between VSWM and math abilities may result in stable across age [ 13 , 69 , 94 , 95 ] or become stronger as a function of age [ 14 , 94 , 95 ], and (ii) there may be a development related shift from verbal to visuo-spatial WM and related strategy used to solving some math tasks [ 45 , 50 , 70 , 71 ], as well as a development related shift from visuo-spatial to both visuo-spatial and verbal WM strategy used to solve math tasks [ 53 , 55 , 95 ]. Moreover, De Vita et al [ 53 ] found that passive VSWM predicts early mathematical knowledge only among preschoolers, while active VSWM predicts math skills in both preschoolers and first-grade children.…”
Section: Discussionsupporting
confidence: 91%
“…Our results, however, suggest the possibility that low-control VSWM also keeps a role in solving math tasks in older children. Our findings regarding the association between VSWM and math in older children are consistent with many studies showing that (i) the association between VSWM and math abilities may result in stable across age [ 13 , 69 , 94 , 95 ] or become stronger as a function of age [ 14 , 94 , 95 ], and (ii) there may be a development related shift from verbal to visuo-spatial WM and related strategy used to solving some math tasks [ 45 , 50 , 70 , 71 ], as well as a development related shift from visuo-spatial to both visuo-spatial and verbal WM strategy used to solve math tasks [ 53 , 55 , 95 ]. Moreover, De Vita et al [ 53 ] found that passive VSWM predicts early mathematical knowledge only among preschoolers, while active VSWM predicts math skills in both preschoolers and first-grade children.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, rote learning and retrieving memorized facts rely more on verbal WM (Van Der Ven et al, 2013). This was corroborated by both empirical studies and meta-analysis, that is, visuospatial WM played a more important role in pupils' geometry abilities and verbal WM had a greater effect on arithmetic abilities (Friso-Van Den Bos et al, 2013 for a meta-analysis; Allen & Giofrè, 2021;Liang et al, 2022).…”
Section: Introductionmentioning
confidence: 86%
“…This was corroborated by ample empirical evidence. In particular, cross‐sectional studies reported that WM capacity contributed to pupils' mathematical achievement (e.g., Blankenship et al, 2018; Cragg et al, 2017; Liang et al, 2022). Longitudinal studies confirmed that kindergarteners' WM capacity shared substantial variance with their mathematical achievement later in primary school (Nguyen & Duncan, 2019; Passolunghi et al, 2008; Xenidou‐Dervou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the WM domains, the use of composite measures of WM had a larger correlation with MP (r = 0.38) than isolated WM-domains alone (verbal WM: r = 30; visuospatial WM: r = 0.31), most likely because these tasks include computational requirements which are predictive of MP, both in the visuospatial and the phonological domains (Swanson and Kim, 2007). Moreover Liang et al (2021) showed that children in the first grade depended more on visuospatial ability than verbal WM, while fifth graders relied on both WM domains in MP situations. These results highlight the progressive and domain specific aspects of WM's influence on MP.…”
Section: Math Anxiety Working Memory and Performancementioning
confidence: 99%